IoT Solutions for Smart Management of Hospital Buildings: A General Review towards COVID-19, Future Pandemics, and Infectious Diseases - Akbarzadeh, Omid; Baradaran, Mehrshid; Khosravi, Mohammad R. (Current Signal Transduction Therapy, 2021)
Background: The paper aims to review existing solutions for smart building to increase hospitality levels in locations like hospitals. The answers could support features such as online appointments, smart navigation, and queue management in the building through mobile phone and navigation to the desired location by highlighting the point of interest and facilities and checking the spaces' occupancy. Methods: Such a solution addresses all mentioned issues regarding the smart building by integrating and utilizing various data sources collected by the internet of things (IoT) sensors. This solution mainly deals with location determining, also known as positioning, using Bluetooth Low Energy radio. The goal is to implement a low-power, low-cost indoor positioning system that utilizes existing hardware. Results: Positions determining is considered a significant section of these kinds of solutions. Previous attempts with indoor positioning systems intensify statistical fingerprinting methods, mainly using IEEE 802.11 (WLAN) as the platform. Conclusions: Some efforts have been made with purely signal strength-based positioning, but indoor environments have been shown to work inauspiciously for these kinds of methods.
Keywords: Internet of things (IoT)